PENGARUH LITERASI DIGITAL, KREATIVITAS, DAN KETERAMPILAN PEDAGOGI TEKNOLOGI TERHADAP PENGGUNAAN LMS MOODLE BAGI GURU SEKOLAH XYZ - Siti Apia; Pujianto Yugopuspito (LPSDI Bina Patria, 2024)
Learning activities must be aligned with the characteristics of current learners to ensure they are ready for the future. The current category of students is Z generation and Alpha where when they are born and grow up very familiar with technology. A challenge for teachers in applying technology in learning activities because it is not just moving learning activities into technology platforms but how to utilize technology in accordance with pedagogic concepts so that learning runs effectively. This study aims to analyze the influence of digital literacy, creativity, and technology pedagogy on the use of Moodle's Learning Management System (LMS) for teachers. This research is quantitative research with Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach, where the data was analyzed using the SmartPLS program version 4.0. involving the entire teacher population in XYZ School totaling 114 people. Data was collected using survey methods using instruments in the form of questionnaires. The results showed that digital iterations and teacher technology pedagogy positively affected the use of the Moodle LMS and there was no relationship between teacher creativity and the use of the Moodle LMS